1989
DOI: 10.1016/0142-694x(89)90021-5
|View full text |Cite
|
Sign up to set email alerts
|

Design discipline and the significance of visuo-spatial thinking

Abstract: This paper discusses the starting points and principles behind two design projects undertaken by students in the Industrial Design Department, Delft University of Technology. The students were included in the design of a hand driven four wheel go-cart and an expresso coffee machine. Preliminary conclusions drawn from the projects were encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 3 publications
(1 reference statement)
2
8
0
Order By: Relevance
“…In alignment with previous findings (e.g., Muller 1989;Henderson 1999;Gonçalves et al 2014), the participants expressed a preference for using visual stimuli for inspirational purposes, despite textual stimuli also being used during the experiment. These novice designers seemed to be aware of how potentially useful distantly related stimuli might be for ideation, as shown also by Ozkan and Dogan's findings (2013).…”
Section: Most Selected Stimuli From the Search Toolsupporting
confidence: 89%
See 1 more Smart Citation
“…In alignment with previous findings (e.g., Muller 1989;Henderson 1999;Gonçalves et al 2014), the participants expressed a preference for using visual stimuli for inspirational purposes, despite textual stimuli also being used during the experiment. These novice designers seemed to be aware of how potentially useful distantly related stimuli might be for ideation, as shown also by Ozkan and Dogan's findings (2013).…”
Section: Most Selected Stimuli From the Search Toolsupporting
confidence: 89%
“…From the myriad of stimuli available to designers, there is a striking preference for visual representations (e.g., Muller 1989;Henderson 1999;Gonçalves et al 2014). This comes as no surprise, as designers are considered to be visualizers (Mednick 1962), and they are considered to be skillful in making and using visual representations.…”
Section: Visual Versus Textual Stimulimentioning
confidence: 99%
“…When searching for information, it is generally known from many studies that designers have a preference for visual ways of information processing and communicating (Gonc alves, Hanington, 2003;Henderson, 1999;Muller, 1989). This preference for visual stimuli is also the reason why designers are considered to be visualizers (Mednick, 1962) and see themselves as highly competent in the use of images.…”
Section: Introductionmentioning
confidence: 94%
“…Tovey [153] who followed a transportation design project found that sketching would often reveal the combination of analytical and holistic processes that the designer employed. Muller [154] also followed students who designed hand-driven go-karts and espresso machines. Martin and Homer [155] collaborated with a resident student in a company that designed glass cutting machines and saw that the disciplined departure from the apparent problem and the application of creative design techniques generated worthwhile results.…”
Section: Other Empirical Approachesmentioning
confidence: 99%